Trade Liberalization and Working Conditions - Bastien Alvarez; Gianluca Orefice; Farid Toubal (CESifo GmbH, 2025)
This paper examines how trade liberalization-induced labor demand shocks affect wages and non-wage working conditions. Using exogenous trade shocks from EU enlargement and worker-level data, we find that export liberalization increases temporary contracts and atypical work schedules, particularly for production workers. However, it has no significant effect on wages, which may reflect firms' ability to expand employment without raising pay due to labor supply elasticity and unemployment. Import liberalization weakly affects working conditions but, consistent with previous studies, lowers wages as firms face stronger competition and reduced labor demand.
Keywords: F15; F16; J30; J51; J81; 330; temporary contracts; working conditions; wages; employment; Eastern European enlargement; trade liberalization